Inducing Bystander Interventions During Robot Abuse with Social Mechanisms - Tan, Xiang Zhi; Vázquez, Marynel; Carter, Elizabeth J.; Morales, Cecilia G.; Steinfeld, Aaron (2018 13th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2018)
We explored whether a robot can leverage social influences to motivate nearby bystanders to intervene and defend them from human abuse. We designed a between-subjects study where 48 participants took part in a memorization task and observed a confederate mistreating a robot both verbally and physically. The robot was either empathetic towards the participant»s performance in the task or indifferent. When the robot was mistreated, it ignored the abuse, shut down in response to it, or reacted emotionally. We found that the majority of the participants intervened to help the robot after it was abused. Interventions happened for a wide range of reasons. Interestingly, the empathetic robot increased the proportion of participants that self-reported intervening in comparison to the indifferent robot, but more participants moved the robot as a response to abuse in the latter case. The participants also perceived the robot being verbally mistreated more and reported higher levels of personal distress when the robot briefly shut down after abuse in comparison to when it reacted emotionally or did not react at all.